Science and the Idea of Social Engineering (II): P. Feyerabend - Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2003)
This article continues the investigation on the relationships between science and social engineering. We inquire and critically analyze the ideas of P. Feyerabend on the social possibilities of science, political role of scientific experts and social engineers. The objective of the article is the reconstruction of Feyerabend’s reception of science and its socio-political role, then, the presentation of Feyerabend’s counter-arguments against Popper’s rationalism and the project of social engineering. According to Feyerabend, an open and free society is the society where every (cultural, religious, epistemological etc.) tradition is provided with equal rights and equal possibilities. Any attempt to impose the standards of one tradition on the others rejects the idea of freedom and liberty. Science is only one epistemological traditions among others, therefore, in a free society scientific standard cannot dominate over the standards of the other traditions. Thus, Feyerabend interprets Popper‘s idea of scientifically grounded social engineering as politically harmful, misleading and incompatible with the requirements of a free society.